Comparison of Polish and Danish approach to promotion of cycling - Okraszewska, Romanika; Jagielska, Zofia (International Conference “Environmental Engineering”, 2017)
The article describes two different approaches to promotion of cycling from Denmark and Poland. In the former the promotion locally from 2009 to 2015 has been supported financially by the national government and where initiatives partly have been financed by the national level. In Poland, the promotion has been implemented often as a result of bottom up initiatives and financed solely on local level often with the support of EU funds. Authors will indicate the strengths of each approach and will formulate recommendations for promoting bike strategy based on the best practices.
Keywords: cycling promotion; cycling strategy